Defective Viral Particles Produced in Mast Cells Can Effectively Fight Against Lethal Influenza A Virus - Huo, Caiyun; Cheng, Jinlong; Xiao, Jin; Chen, Mingyong; Zou, Shumei; Tian, Haiyan; Wang, Ming; Sun, Lunquan; Hao, Zhihui; Hu, Yanxin (Frontiers in Microbiology, 2020)
Mast cells play an important role in the pathogenesis of highly pathogenic H5N1 avian influenza virus (H5N1-HPAIV) infection. Defective viral particles (DPs) can interfere with the replication of infectious viruses and stimulate the innate immune response of host cells. However, DPs arising from mast cells during HPAIV replication and their potent antiviral actions has not been reported. Here, we showed that the human mastocytoma cell line, HMC-1, allowed for the productive replication of the H5N1-HPAIV. Compared with alveolar cell line A549, DPs were propagated preferentially and abundantly in mast cells following IAV infection, which can be attributed to the wide existence of Argonaute 2 (AGO2) in HMC-1 cells. In addition, DPs generated in H5N1-infected cells could provide great therapeutic protection on mice to fight against various influenza A viruses, which included not only homologous H5N1-HPAIV, but also heterologous H1N1, H3N2, H7N2, and H9N2. Importantly, DPs generated in H5N1-infected HMC-1 cells could diminish viral virulence in vivo and in vitro by triggering a robust antiviral response through type II interferon signaling pathways. This study is the first to illustrate the arising of DPs in H5N1-HPAIV infected mast cells and explore their favorable ability to protect mice from influenza A viruses infection, which provides a novel insight and valuable information for the progress of new strategies to fight influenza A viruses infection, especially highly pathogenic avian influenza virus infection by focusing on the DPs generated in mast cells.